1993
DOI: 10.1091/mbc.4.11.1161
|View full text |Cite
|
Sign up to set email alerts
|

The three rows gene of Drosophila melanogaster encodes a novel protein that is required for chromosome disjunction during mitosis.

Abstract: Zygotic expression of the three rows (thr) gene of Drosophila melanogaster is required for normal cell proliferation during embryogenesis. Mitotic defects in thr mutant embryos begin during mitosis 15, and all subsequent divisions are disrupted. Chromosome disjunction and consequently cytokinesis fail during these defective mitoses, although the initial mitotic processes (chromosome condensation, spindle assembly, metaphase plate formation, and cyclin degradation) are not affected. Despite the failure of chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…This pattern of expression, which is initially ubiquitous then restricted to the nervous system (Foe et al, 1993) is very similar to that observed for known cell cycle genes [e.g. three rows, D'Andrea et al (D'Andrea et al, 1993)], consistent with a role for citron in proliferation. The association of citron expression with proliferating tissues contrasts with the widespread expression of another Rho effector kinase rok, and of RhoA, the putative upstream activator of Citron, consistent with Rok and RhoA having roles beyond proliferation (Hariharan et al, 1995).…”
Section: Drosophila Citron Is Expressed In Proliferative Tissues and supporting
confidence: 68%
“…This pattern of expression, which is initially ubiquitous then restricted to the nervous system (Foe et al, 1993) is very similar to that observed for known cell cycle genes [e.g. three rows, D'Andrea et al (D'Andrea et al, 1993)], consistent with a role for citron in proliferation. The association of citron expression with proliferating tissues contrasts with the widespread expression of another Rho effector kinase rok, and of RhoA, the putative upstream activator of Citron, consistent with Rok and RhoA having roles beyond proliferation (Hariharan et al, 1995).…”
Section: Drosophila Citron Is Expressed In Proliferative Tissues and supporting
confidence: 68%
“…pim and thr are not required for centrosome duplication and cytokinesis Our previous phenotypic characterizations of fixed pim and thr mutant embryos had suggested that cytokinesis during mitosis 15 is not completed in these mutants (D'Andrea et al, 1993;Stratmann and Lehner, 1996). Cleavage furrows pinching the undivided chromosomes were often observed in fixed mutant embryos at the stage of mitosis 15.…”
Section: Mitosis 16 But Not Mitosis 15 Is Severely Prolonged In Pim Mmentioning
confidence: 95%
“…After degradation of PIM at the metaphaseto-anaphase transition, SSE promotes sister chromatid separation and also cleaves the associated THR subunit, a process that contributes to timely SSE inactivation (Herzig et al, 2002). We have previously shown that a loss of PIM, THR or SSE function results in a failure of sister chromatid separation during mitosis (D'Andrea et al, 1993;Jäger et al, 2001;Stratmann and Lehner, 1996). In addition, non-cleavable THR versions were shown to interfere with cellularization (Herzig et al, 2002), which corresponds to a modified form of cytokinesis converting the syncytial into the cellularized blastoderm during interphase of cycle 14.…”
mentioning
confidence: 99%
“…Maternally supplied products are sufficient to support cell cycle pro- gression in the Drosophila embryo until G2 of cycle 14, when string gene expression is required. Whereas expression of additional cell cycle genes becomes essential as embryogenesis progresses, to date only five loci have been shown to be essential prior to cycle 17 (string, three rows, pimples, pebble, and the histone locus) (Edgar and O'Farrell 1989;Lehner 1992;D'Andrea et al 1993;Smith et al 1993). …”
Section: Cessation Of D N a Synthesis In De2f M U T A N T Embryosmentioning
confidence: 99%